EFFECT OF LEGUME FODDER ON RUMEN DEGRADATION OF SORGHUM FODDER BY SHEEP - Harande, R. Y.; Muhammad , R. I.; Nasiru, A.; Garba, Y. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
In an agro-pastoral setting where land is a constraint to crop and livestock production, improvement in cereal and legumes for their food value will need to be evaluated for their corresponding improvement for feed. The objective of the study was to examine the effect of legume fodder on degradability of sorghum fodder from improved cereal and legume cultivars. In Sacco rumen degradation technique was used and cultivars of groundnut (samnut23 and samnut26), cowpea (X-IITA) and sorghum (DEKO) were evaluated and examined. Mixed proportions of cereal and legumes as 60:40, 50:50 & 40:60 were ruminally degraded by Yankasa sheep. Results from the experiment unveiled mixture of 50:50 (Deko: samnut26) had better proximate composition, while mixture of 50:50 (Deko:X-IITA) was better in fiber composition. The Potential Degradabilities of both mixtures were 66.94% and 54.46% effectively degraded, respectively. It can be concluded that mixture of 50:50 (Deko: Samnut26) and mixture of 50:50 (Deko:X-IITA) facilitates the effective degradation of sorghum fodder. It is therefore recommended that the cultivars be promoted to farmers and the residue from Deko, haulms from Samnut23 and Samnut26; and X-IITA be fed to sheep at 50:50 for proper residue utilization.